Dynamic Force Production Capacities Between Coronary Artery Disease Patients vs. Healthy Participants on a Cycle Ergometer - Fanget, Marie; Rossi, Jérémy; Samozino, Pierre; Morin, Jean-Benoît; Testa, Rodolphe; Roche, Frédéric; Busso, Thierry; Laukkanen, Jari Antero; Hupin, David (Frontiers in Physiology, 2020)
Background The force-velocity-power (FVP) profile is used to describe dynamic force production capacities, which is of great interest in training high performance athletes. However, FVP may serve a new additional tool for cardiac rehabilitation (CR) of coronary artery disease (CAD) patients. The aim of this study was to compare the FVP profile between two populations: CAD patients vs. healthy participants (HP). Methods Twenty-four CAD patients (55.8 ± 7.1 y) and 24 HP (52.4 ± 14.8 y) performed two sprints of 8 s on a Monark cycle ergometer with a resistance corresponding to 0.4 N/kg × body mass for men and 0.3 N/kg × body mass for women. The theoretical maximal force (F0) and velocity (V0), the slope of the force-velocity relationship (Sfv) and the maximal mechanical power output (Pmax) were determined. Results The Pmax (CAD: 6.86 ± 2.26 W.kg–1 vs. HP: 9.78 ± 4.08 W.kg–1, p = 0.003), V0 (CAD: 5.10 ± 0.82 m.s–1 vs. HP: 5.79 ± 0.97 m.s–1, p = 0.010), and F0 (CAD: 1.35 ± 0.38 N.kg–1 vs. HP: 1.65 ± 0.51 N.kg–1, p = 0.039) were significantly higher in HP than in CAD. No significant difference appeared in Sfv (CAD: −0.27 ± 0.07 N.kg–1.m.s–1 vs. HS: −0.28 ± 0.07 N.kg–1.m.s–1, p = 0.541). Conclusion The lower maximal power in CAD patients was related to both a lower V0 and F0. Physical inactivity, sedentary time and high cardiovascular disease (CVD) risk may explain this difference of force production at both high and low velocities between the two groups.